PENERAPAN UNSUR DAPAT MERUGIKAN KEUANGAN NEGARA DALAM TINDAK PIDANA KORUPSI - Arif Setiawan; Umar Ma’ruf (Jurnal Hukum Khaira Ummah, 2018)
Article 2 and Article 3 of the Law on Corruption should be recognized as the most frequently used article by law enforcement officers in ensnaring corrupt perpetrators who have harmed the State's finances. In the implementation of the element "can harm the state finances" often raises the problem that is 1) Is the element of financial losses of the state in corruption crime is the actual loss or potential loss 2) Who is authorized to calculate and declare that there has been a loss of state finances in the criminal act of corruption 3) How method of calculating the financial losses of the state in the criminal act of corruption. Through normative juridical research by means of research literature then research result that to give more legal certainty and justice, element can harm state finance must be understood as actual loss of state finance (actual loss), while most authorized official in counting loss of state finance is BPK RI by using the method of calculation that is adjusted to the modus operandi. Keywords : harm the state finance